Synthesis of new derivatives of protoporphyrin IX - V. Yu. Pavlov; А. Е. Stepanov; V. I. Shvets (Тонкие химические технологии)
In the course of searching new highly active substances which are prospective for treating tumors and some other types of widespread diseases the synthesis of protoporphyrin IX bearing the benzodiazepine residue, was performed. It was found that the use of porphyrins containing acetylacetonate residues in the heterocyclic synthesis leads to ketone splitting of the acetylacetonate moiety under the mild conditions of regioselective synthesis of benzodiazepine in addition to the formation of porphyrin-benzodiazepines.